PENGARUH DESTINATION IMAGE, DESTINATION SERVICE QUALITY, PERCEIVED VALUE TERHADAP REVISIT INTENTION DENGAN TOURIST SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada Wisata Taman Nasional Bunaken) - Manoppo, Sulistiawati; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT As an archipelagic country with the largest sea area in the world, Indonesia has huge potential to become the global maritime axis. This plays a crucial role for the country’s growth and prosperity. The diverse maritime potential of Indonesia also contributes greatly to the welfare and prosperity of its people. It has a positive impact on the potential of marine tourism in Indonesia, which can contribute to both the national and local economy of the tourist area itself. One of the famous marine attractions in Indonesia is Bunaken National Park. This study aims to analyze the influence of Destination Image, Destination Service Quality, Perceived Value towards Revisit Intention with Tourist Satisfaction as the intervening variable. This study utilizes a quantitative method with a purposive sampling technique. The study population consists of tourists living outside Manado city, with the data collection conducted through online questionnaires. As a result, 168 respondents meet the criteria. Subsequently, the data gathered is being analyzed using the Structural Equation Modelling method with the Analysis Moment of Structural (AMOS) software. The result of the study shows that Destination Image has a significant positive effect on Tourist Satisfaction, Destination Service Quality has a significant positive effect on Tourist Satisfaction, Perceived Value has a significant positive effect on tourist satisfaction, tourist satisfaction has a positive effect on Revisit Intention, Destination Image has no significant positive effect on Revisit Intention , Destination Service Quality has no significant positive effect on Revisit Intention and Perceived Value has no significant positive effect on Revisit Intention.